Upaya Meningkatkan Motivasi Belajar Biologi melalui Model Pembelajaran Guided Inquiry pada Siswa Kelas XI SMA Labschool Jakarta - Juniarto Adi Putra (INTELEKTIUM, 2022)
Through guided inquiry students will prove concepts or theories that already exist and can experience the process or experiment itself, then draw conclusions, so as to support students' understanding of the subject matter. In this case, if students understand more about the subject matter, it is hoped that their learning motivation can increase and have a positive influence on their learning outcomes. This study aims to increase the motivation to learn biology so that students gain knowledge, skills and positive attitude changes. The research was conducted in October - November 2022 at Labschool Jakarta High School. The research subjects were students of class XI IPA 1. The method used was Collaborative Classroom Action Research (CCAR). Data collection techniques were carried out by filling in observation sheets of learning activities, giving motivational questionnaires, and field notes during the learning process. In the pre-cycle data, it was found that 6% of students had low motivation, 70% had moderate motivation, and 24% had high motivation. The results of the first cycle 39% of students have moderate motivation and 61% have high motivation. Whereas for cycle II as much as 21% had moderate motivation and 79% had high motivation. From this study it can be concluded that the guided inquiry learning model can increase the motivation to study Biology in class XI SMA Labschool Jakarta.